Konsep Penganiayaan dalam Matius 10:16-33 dan Respon Orang Percaya Terhadap Penganiayaan - Ado, Ado; Iskandar, Iskandar (Sekolah Tinggi Teologi Immanuel Sintang Kal-Bar, 2021)
This article discusses the biblical concept in Matthew 10:16-33 about persecution. Just as Jesus was persecuted, so in the life of a believer, there is no such thing as being persecuted. Persecution is an act that results in people being injured and can also lose their lives. Persecution is also related to suffering in the lives of believers. The method used in this article uses a qualitative method in which this method is used to examine scientific objects and the author is a key instrument in the researcher. This goal is to mature believers spiritually, create a unity in the body of Christ, the church grows, and evangelism grows to win souls for the glory of His name.